Strategi Guru dan Peran Orang Tua dalam Pengembangan Agama dan Moral Anak di Era Digital - Putri, Hallamatul Hammadah; Rasidi, Rasidi (JEA (Jurnal Edukasi AUD), 2024)
The massive penetration of digital technology in the lives of early childhood has created new challenges in the development of religious and moral values. This study examines teacher strategies, parental roles, and social changes in the development of religious and moral values ​​in PAUD Al Husna Pamekasan. This study uses a phenomenological approach involving four PAUD teachers, five parents, and six children aged 4-6 years. Data were collected through participant observation conducted for three months using interview techniques, and analysis of learning documents. The results of the study indicate that the success of religious and moral development in the digital era requires a balance between traditional values ​​and modern technology. Teachers develop an approach that combines traditional methods with digital technology, while parents apply guided digital parenting that maintains religious values. This study produces three practical implications: a guide to the implementation of balanced teaching methods, an effective teacher-parent communication system, and the development of digital learning materials that support religious and moral values. This study contributes to the development of early childhood education in the digital era while maintaining Indonesian cultural identity.